Piety and responsibility : patterns of unity in Karl Rahner, Karl Barth, and Vedanta Deshika /: patterns of unity in Karl Rahner, Karl Barth, and Vedanta Deshika. (2016) - Sheveland, John N, 1973-
No abstract available